2019
DOI: 10.1249/mss.0000000000001924
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow during Interval and Continuous Exercise in Young and Old Men

Abstract: Purpose Aging is associated with impaired cerebral blood flow (CBF) and increased risk of cerebrovascular disease. Acute increases in CBF during exercise may initiate improvements in cerebrovascular health, but the CBF response is diminished during continuous exercise in older adults. The effect of interval exercise for promoting increases in CBF in young and old adults is unknown. Methods We compared middle cerebral artery blood velocity (MCAv), end-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Authors of 13 studies were contacted twice by e-mail over a 1-month period asking to provide missing data in cases of incomplete reporting. After 1 month, five authors provided more detailed information (Mourot et al, 2004 ; de Carvalho et al, 2014 ; Morales-palomo et al, 2017 ; Pimenta et al, 2019 ), two authors reported no access to the data (Scott et al, 2008 ; Lacombe et al, 2011 ), one author reported the lack of these data (Klein et al, 2019 ), and five authors did not reply.…”
Section: Methodsmentioning
confidence: 99%
“…Authors of 13 studies were contacted twice by e-mail over a 1-month period asking to provide missing data in cases of incomplete reporting. After 1 month, five authors provided more detailed information (Mourot et al, 2004 ; de Carvalho et al, 2014 ; Morales-palomo et al, 2017 ; Pimenta et al, 2019 ), two authors reported no access to the data (Scott et al, 2008 ; Lacombe et al, 2011 ), one author reported the lack of these data (Klein et al, 2019 ), and five authors did not reply.…”
Section: Methodsmentioning
confidence: 99%
“…We are not aware of other neuromodulation device studies that produce such effects. However, the exercise literature, in particular studies of high intensity interval training, does contain examples of time-varying modulation of hemodynamics ( Klein et al, 2019 ). The well-known benefits of aerobic exercise on brain health ( Barnes, 2015 ) makes it an interesting model for comparison as we address future clinical work utilizing tvCVS.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of this study was to investigate the effect of age on the cerebral pressure–flow relationship during repeated stand‐to‐sit transitions. Our main interest in this was to better understand the smaller increase in MCAv, relative to the greater increase in blood pressure, that is consistently reported during exercise in older people (Fisher et al, 2013; Fluck et al, 2014; Klein et al, 2019; Ward et al, 2018). Repeated stand‐to‐sit transitions reflect a common daily movement and are a well‐accepted method to induce dynamic blood pressure changes, which we also demonstrated (Figure 1) (Claassen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Aging and age‐related cerebrovascular diseases are associated with a decline in resting cerebral blood flow, commonly characterized by a lower middle cerebral artery velocity (MCAv), and reduced cerebrovascular function (Ainslie et al, 2008; Bailey et al, 2013; Beek, Olde Rikkert, Pasman, Hopman, & Claassen, 2010). Furthermore, the transient elevation in MCAv during exercise is attenuated in older adults (Fisher et al, 2013; Fluck et al, 2014; Klein, Bailey, Abeln, Schneider, & Askew, 2019; Marsden et al, 2012). Cerebral blood flow control is multifactorial, and it is therefore difficult to isolate the relative regulatory contributions of neural, metabolic, and cardiovascular factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation